Incidence, associated factors and impact of the post-COVID-19 condition in Brazil: Study protocol of an observational cohort during the Omicron phase - Caroline Cabral Robinson; Daniel Sganzerla; Joselia Larger Manfio; Renata Kochhann; Adriana Raquel Binsfeld Hess; Patricia Ferreira da Silva; Nathan Iori Camargo; Andressa Fiorenzano Nunes; Nícolas Taciano Kunkel; Priscila Kieling Binsfeld; Tatiane Aparecida de Miranda; Bruna Machado Barroso; et al. (PLoS ONE, 2025)
The novel coronavirus (SARS-CoV-2) has caused a significant impact in Brazil, with over 37 million cases and 690,000 deaths. Survivors often experience prolonged symptoms, termed post-COVID-19 condition or long COVID, affecting various aspects of life. Data on post-COVID-19 in Brazil, particularly amid the Omicron variant, are limited. This study aims to address this gap by assessing the incidence, associated factors, and impact of post-COVID-19 in adults infected during the Omicron phase, using the World Health Organization case definition. This Brazilian cohort study involves virtual recruitment and a nested case-control design. Participants from all regions will be recruited through electronic announcements. Inclusion criteria comprise age ≥ 18, Brazilian residency, and confirmed symptomatic SARS-CoV-2 infection. A nested case-control study will compare cognitive domains in post-COVID-19 cognitive dysfunction cases and controls. Data collection will utilize standardized instruments, including the EQ-5D-3L, Lawton & Brody Scale, Barthel Index, and others. Statistical analyses will employ adjusted models for primary and secondary outcomes. The study follows ethical guidelines, with an informed consent process tailored to participant preferences. Confidentiality measures include restricted access and secure electronic data storage. Results will be disseminated in academic forums, peer-reviewed journals, and directly communicated to participants. Authorship criteria align with international standards, and data sharing requests will be evaluated by the steering committee. The study is currently recruiting participants.